Learning Divisions of Fractions through Sprint Running Pictures - Abdul Roni; Z. Zulkardi; Ratu Ilma Indra Putri (Intelektual Pustaka Media Utama, 2017)
This study aims to produce Learning Trajectory (LT) that can help students understand the division of fractions in grade 5 elementary schools. This study was conducted on 30 students in class V.e MIN 2 Palembang, South Sumatra Province, Indonesia. This study uses Design Research method with three research stages, namely: 1) Preliminary Design/ preparing for an experiment which is the stage of designing Hyphotecal Learning Trajectory (HLT) and instruments needed, 2) Design Experiment namely HLT test phase consisting of Pilot Experiment and Teaching Experiment and 3) Retrospective Analysis. Instruments for data collections are video recordings, documentation, and interviews, observation sheet, and pre-test and post-test. Hypothetical Learning Trajectory (HLT) of learning division of fractions has been designed into Learning Trajectory (LT) so it can function as a Local Instructional Theory (LIT) which can be developed to provide the materials of the division of fractions for students. The results of this study indicate that the trajectory of learning produced can help students understand the division of fractions. Therefore, it will be able to contribute positively to the various parties who have an interest in the education such as teachers, students, schools and the government. Furthermore, it is also can be used as a reference in the teaching and learning and developing materials of teaching mathematics.